An application of a decomposed ortho-diagonal method to discrete polyoptimization of a hall with spatial grid structure - Paczkowski, Witold M.; Jendo, Stefan (Computer Assisted Methods in Engineering and Science; Vol 6 No 2 (1999), 2023)
The paper deals with application of the ortho-diagonal (O-D) method of finding the non dominated sets of solutions and evaluations for discrete polyoptimization problems. First, the (O-D) method was modified for finding minimum of a scalar function. The mono tonicity property of a vector objective function is used by the (O-D) method for consecutive finding of jth-criteria partial non dominated sets, j € {1, 2, ... ,J}. To find the nondominated evaluations sets the discrete neighbourhoods S of the point Xi are investigated starting from the solution xi which minimizes the first objective function. In this way the consecutive non dominated solutions X k ND are determined. An accuracy of solution and CPU computing time depend on the way the discrete neighbourhoods S of the point x i in the design space are defined. The algorithm of the (O-D) method is applied to solve the discrete polyoptimization of a hall with spatial grid structure.